(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Start-up Ecosystem has gained more importance as it fulfills the gap in the existing market by focusing on the small needs and desires of the customer and the market. The government has also initiated this momentum by developing policy initiatives to promote start-ups and develop necessary skills by passing clear plans to strengthen the entrepreneurial ecosystem in the country. In recent years, start-ups have received increased attention in many parts of the world. In India, the number of start-ups has increased fast, and more support has become available in all dimensions. The Indian youth are the torchbearers of this system. This paper analyses the state of the Indian start-up ecosystem and college students’ awareness level. It also focuses on the government initiatives taken for the start-up ecosystem. This paper also analyses the challenges faced by start in the Indian ecosystem. The analysis uses data collated from semi-structured interviews through the questionnaire method. In addition, a survey of relevant literature adds to the analysis of the study.